Leaf Area Index and Biomass Assessment over Tropical Peatland Forest Ecosystem Using ALOS PalSAR and Envisat ASAR Dat - Wijaya, Arief (2011)
Provision of accurate forest parameter properties is important as a basis for forest resources monitoring and carbon cycle assessment. The present study aims to model leaf area index (LAI), above ground biomass and carbon stocks over tropical peatland forests using single polarization SAR, full polarimetry SAR (PolSAR) data. Single band ALOS Palsar data (HH band, acquired on November 17, 2008) and polarimetric data (HH, VV, HV and VH, collected on April 4 and May 5, 2007) are used for the study. A series of ENVISAT ASAR data (5 datasets) collected in 2004 – 2005 are also used to model the forest properties. Landsat ETM data collected on January 22, 2009 is also used as a reference. The relationship between forest parameters and normalized radar backscattering is estimated using empirical models, and preliminary results show that Polarimetric SAR data has better correlations with the LAI and biomass than single polarimetry SAR data. The field data were collected during field work in March – April 2009 and the reliability of identified forest classes was also assessed from available Landsat ETM data. Analysis will be conducted on the basis of statistical correlations between radar data and modeled forest properties, such as LAI, biomass and tree age. This study focuses on a unique tropical peatland ecosystem in Kampar Peninsula, Sumatera, Indonesia, which has great potentials as carbon sinks and/or sources. Only few studies have been conducted in the study area due to limited satellite and field observation data.